Eusiridae - Coleman, Charles Oliver (Zootaxa, 2009)
An eusirid amphipod was found around Lizard Island on the Great Barrier Reef. It is described as Tethygeneia aff. pacifica. It has large eyes. Gnathopods 1 and 2 are subequal, their carpal lobes are only weakly produced, and carpus and propodus are subequal in length on both appendages. The telson is only weakly tapering distally and has wide rounded apices.